Molecular analysis of ivy cells of the hippocampal CA1 stratum radiatum using spectral identification of immunofluorophores - Somogyi, Jozsef; Szabo, Andras; Somogyi, Peter; Lamsa, Karri P. (Frontiers in Neural Circuits, 2012)
Neuronal nitric oxide synthase-expressing (nNOS+) GABAergic interneurons are common in hippocampal stratum (str.) radiatum. However, these cells are less well characterized than nNOS+ ivy cells in str. pyramidale or neurogliaform cells (NGC) in str. lacunosum-moleculare. Here we have studied the laminar distribution of the axons and dendrites, and the immunoreactivity of these neurons recorded in rat hippocampal slices. We have used spectral analysis of antibody- or streptavidin-conjugated fluorophores to improve recognition of genuine signals in reactions for molecules such as nNOS and neuropeptide-Y (NPY). We found that most nNOS+ cells with soma in the CA1 area str. radiatum exhibit characteristic properties of ivy cells, and were positive for NPY and negative for reelin. However, laminar distributions of their neurites differ from original characterization of ivy cells with the soma in or close to str. pyramidale. Both their dendrites and axon are mainly in str. radiatum and to a lesser extent in str. oriens, and in addition often extend to str. lacunosum-moleculare. We conclude that ivy cells in str. radiatum may predominantly be feedforward inhibitory interneurons in the CA1 area, and their axonal output delivering GABA, NPY, and NO can influence both the entorhinal cortex innervated and the CA3 innervated zones pre- and post-synaptically. Spectral analysis of fluorophores provides an objective algorithm to analyze signals in immunoreactions for neurochemical markers.